STRUCTURAL COMPONENTS OF THE FISCAL MECHANISM FOR REGULATING THE INVESTMENT PROCESSES - Melnik, V.M.; Rudenko, V.V. (The actual problems of regional economy development, 2021)
The influence of the fiscal mechanism on investment processes is carried out through its structure and the focus of the components on solving specific problems and achieving a real effect, which occurs due to financial resources that are formed, distributed and used to meet the investment needs of economic entities. This determines the relevance of the study of the structural components of the fiscal mechanism and their impact on investment. The article is devoted to the separation and substantiation of the structural components of the fiscal mechanism for regulating the investment processes. The specifics of scientific tasks being the subject of the research required the use of a complex of methods which enabled to determine the structural components of the fiscal mechanism for regulating the investment processes, including methods, forms, tools and levers. The article the content of the methods of the fiscal mechanism for regulating the investment processes is investigated and it is proposed to include planning, organization and control among them. The essence of the forms of fiscal mechanism for regulating the investment processes is considered and their structure is substantiated, covering the tax form of mobilization of budget revenues, non-tax form of mobilization of budget revenues, transfer, budget financing, budget investment, budget reservation, budget financing, budget crediting, state (local) borrowings. state (local) guarantees. The content of the instruments of the fiscal mechanism for regulating the investment processes is determined and it is recommended to include revenues, expenditures, budget balancing and state (local) borrowings. The essence of the levers of the fiscal mechanism for regulating the investment processes is highlighted and it is proposed to include the means by which the effect of fiscal instruments is enhanced, which can be both stimulating and deterrent. As a result of the research it is proved that the fiscal mechanism for regulating the investment processes is a set of methods, forms, tools and levers of state influence on the formation, distribution and use of financial resources to implement fiscal policy aimed at irreversible, targeted, quantitative, structural and qualitative socio-economic changes due to the implementation of investments.